Identification and functional analysis of two new de novo KCNMA1 variants associated with Liang–Wang syndrome. (23rd February 2022) - Liang, Lina; Liu, Huihui; Bartholdi, Deborah; van Haeringen, Arie; Fernandez‐Jaén, Alberto; Peeters, Els E. A.; Xiong, Hongbo; Bai, Xuemei; Xu, Chengqi; Ke, Tie; Wang, Qing K.
Abstract: Aim: Loss‐of‐function KCNMA1 variants cause Liang–Wang syndrome (MIM #618729), a newly identified multiple malformation syndrome with a broad spectrum of developmental and neurological phenotypes. However, the full spectrum of clinical features and underlying pathogenic mechanisms need full elucidation. Methods: Exome sequencing was used to identify pathogenic variants. Patch‐clamp recordings were performed to access the effects of KCNMA1 variants on BK channels. Total and membrane protein expression levels of BK channels were characterized using Western blotting. Results: We report identification and functional characterization of two new de novo loss‐of‐function KCNMA1 variants p.(A172T) and p.(A314T) with characteristics of Liang–Wang syndrome. Variant p.(A172T) is associated with developmental delay, cognitive impairment and ataxia. Mechanistically, p.(A172T) abolishes BK potassium current, inhibits Mg 2+ ‐dependent gating, but shifts conductance‐voltage (G‐V) curves to more positive potentials when complexed with WT channels. Variant p.(A314T) is associated with developmental delay, intellectual disability, cognitive impairment, mild ataxia and generalized epilepsy; suppresses BK current amplitude; and shifts G‐V curves to more positive potentials when expressed with WT channels. In addition, two new patients with previously reported gain‐of‐function variants p.(N536H) and p.(N995S) are found to show epilepsy and paroxysmal dyskinesia as reported previously, but also exhibit additional symptoms of cognitive impairment and dysmorphic features. Furthermore, variants p.(A314T) and p.(N536H) reduced total and membrane levels of BK proteins. Conclusion: Our findings identified two new loss‐of‐function mutations of KCNMA1 associated with Liang–Wang syndrome, expanded the spectrum of clinical features associated with gain‐of‐function KCNMA1 variants and emphasized the overlapping features shared by gain‐of‐function and loss‐of‐function mutations.